2012
DOI: 10.1002/chem.201200547
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalysed Enantioselective Addition of OH and NH Bonds to Allenes: A New Model for Stereoselectivity Based on Noncovalent Interactions

Abstract: The ability of silver complexes to catalyse the enantioselective addition of O-H and N-H bonds to allenes is demonstrated for the first time by using optically active anionic ligands that were derived from oxophosphorus(V) acids as the sources of chirality. The intramolecular addition of acids, alcohols, and amines to allenes can be achieved with up to 73% ee. The exploitation of a C-H anomeric effect allowed the absolute configuration of a sample of 2-substituted tetrahydrofuran of low ee to be unambiguously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…In summary, the computational results indicate that high enantioselectivities could arise even in covalent catalysis from a sum of attractive noncovalent interactions. Although the role of noncovalent interactions in controlling enantioselectivity has been noted before in organocatalysis17 and metal catalysis,24 we believe ours is the first documented example of covalent catalysis in which attractive noncovalent interactions appear to be in full control of the enantioselectivity.…”
Section: Resultsmentioning
confidence: 50%
“…In summary, the computational results indicate that high enantioselectivities could arise even in covalent catalysis from a sum of attractive noncovalent interactions. Although the role of noncovalent interactions in controlling enantioselectivity has been noted before in organocatalysis17 and metal catalysis,24 we believe ours is the first documented example of covalent catalysis in which attractive noncovalent interactions appear to be in full control of the enantioselectivity.…”
Section: Resultsmentioning
confidence: 50%
“…32 Enantioselectivities up to 73%ee 30 were obtained with oxophosphorous(V) phosphinate (β-CgPOOH) and phosphate (TADDOL-POOH) complexes of silver, by weakly attractive non-covalent interactions between the ligand and the substrate in the transition state structures. The reaction works for γ-allenols and γ-allenic acids to form 35 tetrahydrofurans or lactones respectively (Scheme 29).…”
Section: Scheme 27mentioning
confidence: 99%
“…32 In comparison with the reaction of the oxygen derivatives, γ-amino allenes gave slower reactions, probably due to slow proton transfer after 60 cyclisation (see Scheme 28). It was found that pyridine speeds up the reaction with the β-CgPOOAg complex, giving the product in 24 h with up to 68% ee (Scheme 45).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Prior to this, Ag-catalysed reactions of (relatively unactivated) alkynes were limited to the addition of alkyl and aryl amine substrates. [10][11][12][13][14][15][16] Using unsubstituted 1a as the model substrate, a total of eleven silver salts AgX or Ag 2 Y were initially assessed using DCE as the solvent, where X = OAc, TFA, NO 3 , SbF 6 , PF 6 , BF 4 , OTf, OTs; Y = CO 3 , O, SO 4 (Table S1 in the ESI, † with selected examples given in Table 1).…”
mentioning
confidence: 99%